STRATEGY TO MAINTAIN EMPLOYEE WELLBEING IN THE COVID-19 PANDEMIC TIME - Naik Henokh Parmenas (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2021)
The study used a random questionnaire that had been distributed to employees from various types of businesses, there were 157 respondents who filled in, and 134 data were processed by the author to analyze the company's strategy in maintaining employee well-being. Among them are: Demographics of respondents consisting of: Type of business entity, type of industry, size of company. In addition, we took data about the impact of the Covid-19 pandemic on companies. Strategies for maintaining employee well-being which include: a) implementation of strategies consisting of: types of wellbeing programs implemented by the company, description of the implementation of well-being programs before and after the Covid-19 pandemic. b) Dynamic implementation of strategies for maintaining employee wellbeing based on dimensions consisting of: application of wellbeing to improve physical health, psychological health, relationship, homework interface. Research result; an increase in the percentage of companies implementing well-being programs from 58% to 63%. The strategy applied by the company focuses more on the wellness program. Based on the dimensions of Employee well-being, companies implement more Physical Health programs by providing health care (masks, vitamins, hand sanitizers) and the lowest is Psychological Health.